PEIZOELECTRIC SENSOR MODEL TO UNLOCK DIGITAL DOORS USING ARDUINO UNO - M. Rasyid; Fitra Yuda; Retchi Puspita (STMIK Royal, 2024)
Abstract: Generally, people still use a simple key system. The door opening function still uses conventional (manual) keys such as locking levers, sliding locks or rotating hinges. The widespread use of keys as a general security method often results in the loss of keys while traveling. For this reason, this research aims to maintain a home or place security system that must be protected with a knock sensor at an affordable price among the public. This system uses a knock key piezoelectric sensor, Arduino Uno. So it produces a smart door using a knock sensor, where when it is knocked the knock is automatically read by the sensor. Keywords: knock piezoelectric sensor; arduino uno. Abstrak: Umumnya masyarakat masih menggunakan sistem kunci yang sederhana. Fungsi bukaan pintu masih menggunakan kunci konvensional (manual) seperti tuas pengunci, kunci geser atau engsel putar. Meluasnya penggunaan kunci sebagai metode keamanan umum seringkali mengakibatkan hilangnya kunci saat bepergian. Untuk itu penelitian ini bertujuan untuk menjaga sistem keamanan rumah atau tempat yang harus dilindungi dengan sensor ketukan dengan harga yang terjangkau dikalangan masyarakat. Sistem ini menggunakan sensor piezoelektrik kunci ketuk, arduino uno. Sehingga menghasilkan pintu pintar dengan menggunakan sensor ketukan, dimana ketika diketuk otomatis ketukan itu terbaca dengan sensor tersebut. Kata kunci: sensor piezoelektrik kunci ketuk; arduino uno.